2018
DOI: 10.4028/www.scientific.net/ssp.280.433
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Reduction of Iron Ore with Carbonaceous Materials

Abstract: An investigation on the reduction of iron ore with carbonaceous material as a reductant was carried out at 1550°C. Iron ore was mixed with biochar from palm shell and coke as a reference at C/O molar ratio of 1.0. Characterisation of raw materials was performed using X-ray Fluorescence (XRF), Brunauer–Emmett–Teller (BET), Fourier Transmittance Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD) and Scanning Electron Microscope (SEM-EDX). The samples after reduction were characterised to study the phase trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The crystalline phases found in RP were identified by the presence of characteristic peaks of Ca, Si, Fe and Zn oxides (the most abundant elements obtained by ICP). Nevertheless the peaks of the fresh catalyst are more intense than those of the spent catalyst and a new small peak of graphitic carbon appears on the spent material [69,70] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystalline phases found in RP were identified by the presence of characteristic peaks of Ca, Si, Fe and Zn oxides (the most abundant elements obtained by ICP). Nevertheless the peaks of the fresh catalyst are more intense than those of the spent catalyst and a new small peak of graphitic carbon appears on the spent material [69,70] …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless the peaks of the fresh catalyst are more intense than those of the spent catalyst and a new small peak of graphitic carbon appears on the spent material. [69,70] In the case of NiMo/Al the X-ray diffraction peaks of Ni (2θ = 44.5°and 51.8°) [71] and Mo (2θ = 40.5°and 50.7°) [72][73][74] species were not detected but small peaks of Ni at 2θ = 44.5°and Mo at 2θ = 40.5°were seen in the diffractogram of the fresh catalyst. γ-Al 2 O 3 peaks of the fresh catalyst at 2θ = 37.7°, 45.9°and 66.9°h ad a slightly higher intensity than those of the spent catalyst in which also the graphitic carbon peak was detected.…”
Section: Coke Depositionmentioning
confidence: 91%
“…Biochar is produced by heating a biomass feedstock in the absence of oxygen. Examples of biochar applications include carbon sequestration, [1] soil amendment, [2][3][4] activated carbon for water [5][6][7] or gas purification, [8,9] biocoke fuel source for metallurgical applications, [10][11][12] filler for composite/polymer materials [13,14] or concrete, [15] and electrode material for batteries and supercapacitors. [16,17] Industrial pyrolysis reactors for the production of biochar from biomass can be classified according to how quickly the biomass particles are heated.…”
Section: Introductionmentioning
confidence: 99%
“…Partial replacement of coke by bio-coals and raw biomass in self-reducing mixtures or composites is reported in the literature [16][17][18][19][20][21][22][23][24][25][26][27]. The effect of the C/O molar ratio on the reduction behavior of iron ore has been studied earlier [16,24,25]. Najmi et al [16] found that the reduction of iron oxide was enhanced when using pyrolized bio-coal in a composite tested isothermally at 1550 • C when compared to composites containing only coke.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the C/O molar ratio on the reduction behavior of iron ore has been studied earlier [16,24,25]. Najmi et al [16] found that the reduction of iron oxide was enhanced when using pyrolized bio-coal in a composite tested isothermally at 1550 • C when compared to composites containing only coke. Liu et al [24] studied the reduction behavior of bio-coal containing iron oxide composite pellets.…”
Section: Introductionmentioning
confidence: 99%